2003
DOI: 10.1046/j.1525-1497.2003.20207.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of current guidelines for primary prevention of coronary heart disease

Abstract: OBJECTIVE:In primary prevention of atherosclerotic disease, it is difficult to decide when medical treatment should be initiated. The main goal of the study was to compare different guidelines for coronary heart disease (CHD) risk assessment and initiation of lipid-lowering therapy. RESULTS: Guidelines could be applied to different subsets of the cohort, ranging from 22% (PROCAM) to 95% of the cohort (revised Sheffield table). All guidelines (except PROCAM) could be applied to a total of 62 patients. Guideline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…11,12 A Swiss study using the PCE and European SCORE risk estimates found that more adults qualified for statin therapy based on the U.S. PCE 10-year predicted risk than under the European guidelines. 6 This finding is not surprising, given the ACC/AHA and ESC/EAS guidelines use different risk thresholds for statin recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A Swiss study using the PCE and European SCORE risk estimates found that more adults qualified for statin therapy based on the U.S. PCE 10-year predicted risk than under the European guidelines. 6 This finding is not surprising, given the ACC/AHA and ESC/EAS guidelines use different risk thresholds for statin recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The basis of the diagnostic pyramid described was a clinical examination, the patient's history, and the use of established risk scores, such as those used in the Framingham 27 and PROCAM (prospective cardiovascular Munster) studies. 28 Since these allow for calculation of relative risk only, implying that only a certain percentage of a patient population obviously is at risk, additional diagnostic efforts are required to characterise the vulnerable patient further.…”
Section: Non-invasive Determination Of Plaque Morphology By Msctmentioning
confidence: 99%
“…Current guidelines in the world recommend lipid-lowering therapy by specific drugs, if the absolute risk exceeds a certain threshold (18). The threshold is 20% over 10 years according to the joint European Societies guidelines (4, 5) and 15% over 10 years according to the joint British guidelines (6).…”
Section: Discussionmentioning
confidence: 99%